(untitled) (Fiep Bulletin - online, 2013)
For this study beyond the general objectives of assessing the age of children with motor problems distorted picture and the relation of childhood obesity with motor problems, we aim to evaluate the specific perception that children images of themselves, evaluate the motor age Children who present proper image and compare the motor age of children who have distorted and 18 children participated adequate picture of both sexes aged 7 years enrolled in a private school in the city of Manaus / AM. The subjects were divided into two groups: 09 in the control group containing children identified with proper image and 09 in the experimental group containing children identified with distorted picture. The perception of body image of the subjects was assessed through a questionnaire and identification of body mass index. This questionnaire is themed "Lifestyle of young Luso-Brazilian" and was developed by Professors Portuguese. The body mass index (BMI) of the subjects was also conducted. To identify the motor age used the evaluation protocol Motor Development Scale (EDM). The results indicated that both groups show similarity between the motor age and chronological age and overall classification average normal, however, observed that over the coarse motor test, which indicates motor coordination, the control group had the best results. In the test of body schema only the experimental group received below the motor age and chronological data significativamentes different, indicating that the group has distorted picture has worst body orientation. In BMI significant difference found, the subjects in the experimental group were found overweight, while the other is normal weight. These data lead us to believe that children have distorted body image may have excess weight and also motor problems.